If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3x = 4x + -6 Reorder the terms: 15 + 3x = -6 + 4x Solving 15 + 3x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + 3x + -4x = -6 + 4x + -4x Combine like terms: 3x + -4x = -1x 15 + -1x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -1x = -6 + 0 15 + -1x = -6 Add '-15' to each side of the equation. 15 + -15 + -1x = -6 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = -6 + -15 -1x = -6 + -15 Combine like terms: -6 + -15 = -21 -1x = -21 Divide each side by '-1'. x = 21 Simplifying x = 21
| 44988*93,921=43985*92,781+1003*a | | 2x^2-24=-2x | | y=6x+2-7x^2 | | -2x-3=4x+15 | | 10b^2+43b-9= | | 37-5*6+4= | | x^3+y^3=72 | | cos^2=0.25 | | X+5+10=60 | | 1-(3x-8)=8 | | 6b^2-12b-58=0 | | y=5cos^2x+3 | | z^2+2z-2i+1=0 | | (sinx+1)(cosx-2)=0 | | 3n^2-6n-9=0 | | 0.57=logx | | 3n^2+12n-90=-8 | | k^2-4k-60=0 | | 9x+9y+18=0 | | 6y-3=5-2y | | 7x-14=-7x | | 66-(4x+12)=4(x+9)+x | | 10-5x=2(5x-10) | | 0.03x+0.05(2000-x)=99.5 | | 22x-23Y=21 | | 4=6x-3+7 | | e^5x-1=12 | | 24+5y=9y | | 8x+3(2x-1)=5x+6 | | 22=2w-8 | | 3(x-4)=5(x-6) | | K-9=-11 |